Naturalizing Husserlian Phenomenology along a Leibnizian Pathway. - Petit, Jean-Luc (Avant, 2014)
A contribution to the history of a formerly hotly discussed, but short-lived scientific project: neurophenomenology 52, the proposal of weaving together Husserlian phenomenology of consciousness and the neuroscience of brain functioning, this article traces back the opening and closing of an apparent window of opportunity, both in phenomenology and in neuroscience, for the eventually unfulfilled realization of that project.